Nutrient source (vegan vs. omnivorous diet) : impact on the recovery of muscle function and performance after damaging exercise : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Duncan, Ben (Massey University, 2023)
Purpose: This study investigated if the source of nutrients from vegan and omnivorous diets affects the recovery of muscle function and performance following damaging exercise. Methods: Three (3) vegans (mean age 32.3 ± 5.77 years; 63.4 ± 16.9 kg; 173.7 ± 9.5 cm) and seven (7) omnivores (mean age 25 ± 5.35 years; 70.9 ± 8.5 kg; 167.9 ± 8.2 cm) underwent a muscle-damaging exercise protocol involving 200 drop jumps. At baseline, and 0 h, 1 h, 3 h, 24 h, 48 h, and 72 h post-exercise maximal isometric voluntary contraction (MIVC), rate of force development (RFD), countermovement jump height (CMJ), pressure pain threshold (PPT), pain at rest (overall and by specific muscle), and pain during CMJ and MIVC were measured to assess muscle function, performance and soreness. Participants followed a macronutrient-matched meal plan and consumed a standardised meal post-exercise. Results: A significant interaction effect of time x diet on Pain Rest, and Pain MIVC existed. Post-hoc analysis found significantly lower MIVC in vegans at 24 h (P = 0.04), Pain Rest to be significantly higher in vegans at 3 h (P = 0.02), Pain during CMJ (P = 0.015) and MIVC (P = 0.02) at 24 h was significantly higher in vegans as well as Pain during MIVC at 3 h (P = 0.02), PPT Rectus Femoris at 1 h significantly higher in omnivores, and vegans experienced significantly sorer left (P=0.016) and right (P=0.015) calves, left (P=0.039) and right (P=0.039) inner thighs, and left (P=0.02) and right (P=0.025) outer thighs at 3h. A significant main effect of time on MIVC, CMJ, Pain Rest (overall and by muscle), Pain CMJ and MIVC, PPT Rectus Femoris, PPT Vastus Lateralis, and PPT Vastus Medialis. No significant main effects of diet were found. Although, ‘large’ effect sizes existed for many variables. Most nutrients involved in muscle recovery showed no differences between diets other than Vitamin C with near significance (P = 0.054). Based on current literature, other nutrients that may have differed but were not quantified in this study were Creatine, L-Carnitine, Vitamin D, Anthocyanins, and Ellagitannins. Conclusion: It appeared that the omnivore diet group experienced lower reductions in MIVC as compared to the vegan diet group who experienced increased pain at rest (overall and by muscle group) and during activity. The small sample size likely prevented the findings of this study from reaching statistical significance so further, more powerful research addressing this study’s limitations should be performed before recommendations can be made.
Keywords: 321006 Sport and exercise nutrition